ANTIBACTERIAL, IN VITRO CYTOTOXIC, AND ANTIOXIDANT ACTIVITIES OF ELECTROLYZED OXIDIZING/REDUCING WATER - DJALIL, ASMIYENTI DJALIASRIN; SUNDHANI, ELZA; WAHYUNINGRUM, RETNO; HARTANTI, DWI; LESTIOWATI, NONI; PANGESTU, PRAYOGO; SETIAJI, RIDWAN; SUWANDRI, SUWANDRI (International Journal of Applied Pharmaceutics, 2019)
Objective: Electrolyzed oxidizing/reducing water is popular as health beneficial water in Indonesia. In this study, we examined the level of antibacterial, anticancer, and antioxidant activity of the electrolyzed water. Methods: The efficacy of electrolyzed water produced by Enagic® at six level pH (2.5, 6.0, 7.0, 8.5, 9.0, and 9.5) was investigated. Antibacterial activity was evaluated using a macrodilution method. The anticancer activity was performed against human breast cancer (T47D) cell lines using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay. Moreover, the antioxidant activity was determined using antioxidant model, 2,2-diphenyl-1picrylhydrazyl radical scavenging activity. Results: The results show that electrolyzed water exhibited antibacterial activity against Propionibacterium acnes and Staphylococcus epidermidis. Among six level pH, electrolyzed water at pH 2.5 showed the highest antibacterial activity. The in vitro cytotoxic activity of electrolyzed water showed potential moderate cytotoxicity. The activity tends to be higher in alkaline electrolyzed water. However, the electrolyzed water showed free radical scavenging activity. Conclusion: Electrolyzed water that marked in Indonesia has some potential health benefits. The activity is dependent on pH.